β-(4-fluorobenzyl) Arteannuin B induced interaction of ATF-4 and C/EBPβ mediates the transition of breast cancer cells from autophagy to senescence - Mir, Khalid Bashir; Faheem, Mir Mohd; Ahmad, Syed Mudabir; Rasool, Javeed Ur; Amin, Tanzeeba; Chakraborty, Souneek; Bhagat, Madhulika; Ahmed, Zabeer; Ali, Asif; Goswami, Anindya (Frontiers in Oncology, 2022)
ATF-4 is a master regulator of transcription of genes essential for cellular-adaptive function. In response to the quantum and duration of stress, ATF-4 diligently responds to both pro-apoptotic and pro-survival signals converging into either autophagy or apoptosis/senescence. Despite emerging cues implying a relationship between autophagy and senescence, how these two processes are controlled remains unknown. Herein, we demonstrate β-(4-fluorobenzyl) Arteannuin B (here after Arteannuin 09), a novel semisynthetic derivative of Arteannuin B, as a potent ER stress inducer leading to the consistent activation of ATF-4. Persistent ATF-4 expression at early time-points facilitates the autophagy program and consequently by upregulating p21 at later time-points, the signaling is shifted towards G2/M cell cycle arrest . As bZIP transcription factors including ATF-4 are obligate dimers, and because ATF-4 homodimers are not highly stable, we hypothesized that ATF-4 may induce p21 expression by physically interacting with another bZIP family member i.e., C/EBPβ. Our co-immunoprecipitation and co-localization studies demonstrated that ATF-4 is principally responsible for the autophagic potential of Arteannuin 09, while as, induction of both ATF-4 and C/EBPβ is indispensable for the p21 regulated-cell cycle arrest. Interestingly, inhibition of autophagy signaling switches the fate of Arteannuin 09 treated cells from senescence to apoptosis. Lastly, our data accomplished that Arteannuin 09 is a potent inhibitor of tumor growth and inducer of premature senescence in vivo.